Catalytic hydrothermal liquefaction of water hyacinth. (February 2015) - Singh, Rawel; Balagurumurthy, Bhavya; Prakash, Aditya; Bhaskar, Thallada
Highlights: Water hyacinth valorization through hydrothermal liquefaction is successfully performed. Reaction conditions were optimized for high bio-oil yield. Thorough bio-oil analysis using 1 H and 13 C NMR. Bio-oil with high aliphatic and aromatic content was obtained. Alkaline catalysts enhanced both quality and quantity of bio-oil. Abstract: Thermal and catalytic hydrothermal liquefaction of water hyacinth was performed at temperatures from 250 to 300 °C under various water hyacinth:H2 O ratio of 1:3, 1:6 and 1:12. Reactions were also carried out under various residence times (15–60 min) as well as catalytic conditions (KOH and K2 CO3 ). The use of alkaline catalysts significantly increased the bio-oil yield. Maximum bio-oil yield (23 wt%) comprising of bio-oil1 and bio-oil2 as well as conversion (89%) were observed with 1 N KOH solution. 1 H NMR and 13 C NMR data showed that both bio-oil1 and bio-oil2 have high aliphatic carbon content. FTIR of bio-residue indicated that the usage of alkaline catalyst resulted in bio-residue samples with lesser oxygen functionality indicating that catalyst has a marked effect on nature of the bio-residue and helps to decompose biomass to a greater extent compared to thermal case.